ENCOURAGING INFLUENCE IN THE MANAGEMENT OF INNOVATION AND PEDAGOGICAL ACTIVITIES (Web of Teachers: Inderscience Research, 2025)
In the article the system of methods that provides the motivating impact in the management of innovative pedagogical activities is proposed. The author reveals integrative features of various combinations of the methods and possibilities of their application in the management of pedagogical innovations.